The Integral Role of CD74 in Antigen Presentation, MIF Signal Transduction, and B Cell Survival and Homeostasis - Bucala, Richard; Shachar, Idit (Mini Reviews in Medicinal Chemistry, 2014)
Molecules that link innate and adaptive immunity and regulate immune response in health and disease are now the focus of many studies. This review discusses CD74 and its ligand macrophage migration inhibitory factor (MIF), and their central position in linking these two components of the immune response by controlling survival of macrophages and B cells.
Keywords: MIF